2022
DOI: 10.7150/ijbs.77126
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gαi3 as a novel molecular therapeutic target of cervical cancer

Abstract: Here we studied expression and potential functions of Gαi3 in cervical cancer. The bioinformatics analysis together with the results from local patients' tissues revealed that Gαi3 expression was remarkably elevated in human cervical cancer tissues and different cervical cancer cells, and was associated with poor overall survival and poor disease-specific survival of patients. Gαi3 depletion resulted in profound anti-cervical cancer activity. In primary or immortalized cervical cancer cells, Gαi3 shRNA or CRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…It has been shown that targeted inhibition of Gαi2 in cardiomyocytes enhanced ischemic stress-induced oxidative [ 39 ]. Moreover, transcription factors binding to antioxidant response elements (ARE) could promote the transcriptional activation of Gαi2 [ 18 ]. These studies implied a potential role of Gαi2 in antioxidant response.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that targeted inhibition of Gαi2 in cardiomyocytes enhanced ischemic stress-induced oxidative [ 39 ]. Moreover, transcription factors binding to antioxidant response elements (ARE) could promote the transcriptional activation of Gαi2 [ 18 ]. These studies implied a potential role of Gαi2 in antioxidant response.…”
Section: Resultsmentioning
confidence: 99%
“…In osteosarcoma, overexpressed Gαi3 associated with multiple RTKs to mediate downstream Akt signaling activation, driving osteosarcoma cell growth [ 19 ]. Moreover, upregulated Gαi3 is a promising novel oncotarget of cervical cancer [ 18 ]. Gαi3 silencing or KO potently inhibited cervical cancer cell growth in vitro and in vivo [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCK-8, colony formation, “Transwell” cell migration and “Matrigel Transwell” invasion assays, were reported early 21 , 30 - 34 . The caspase activity assay, Histone DNA ELISA, nuclear TUNEL fluorescence staining and JC-1 monomer staining of mitochondrial depolarization were reported early 21 , 30 - 35 . mRNA detection by qRT-PCR and protein detection by Western blotting were reported previously 21 , 30 - 34 .…”
Section: Methodsmentioning
confidence: 99%